2013 White Paper on recent issues in bioanalysis: 'hybrid' – the best of LBA and LCMS. (December 2013) - Stevenson, Lauren; Garofolo, Fabio; DeSilva, Binodh; Dumont, Isabelle; Martinez, Suzanne; Rocci, Mario; Amaravadi, Lakshmi; Brudny-Kloeppel, Margarete; Musuku, Adrien; Booth, Brian; Dicaire, Catherine; Wright, Laura; et al.
The 2013 7th Workshop on Recent Issues in Bioanalysis was held in Long Beach, California, USA, where close to 500 professionals from pharmaceutical and biopharmaceutical companies, CROs and regulatory agencies convened to discuss current topics of interest in bioanalysis. These 'hot' topics, which covered both small and large molecules, were the starting point for fruitful exchanges of knowledge, and sharing of ideas among speakers, panelists and attendees. The discussions led to specific recommendations pertinent to bioanalytical science. Such as the previous editions, this 2013 White Paper addresses important bioanalytical issues and provides practical answers to the topics presented, discussed and agreed upon by the global bioanalytical community attending the 7th Workshop on Recent Issues in Bioanalysis.